Antibodies to Endothelial Cell Growth Factor and Obliterative Microvascular Lesions in the Synovium of Patients With Antibiotic‐Refractory Lyme Arthritis. Issue 8 (August 2014) - Londoño, Diana; Cadavid, Diego; Drouin, Elise E.; Strle, Klemen; McHugh, Gail; Aversa, John M.; Steere, Allen C.
<x xml:space="preserve">Abstract</x> Objective Endothelial cell growth factor (ECGF) was recently identified as the first autoantigen known to be a target of T cell and B cell responses in ∼20% of patients with antibiotic‐refractory Lyme arthritis. The goal of the current study was to look for a pathologic correlate between ECGF autoantibody responses and histologic findings in synovial tissue. Methods Synovial tissue was examined from 14 patients with antibiotic‐refractory Lyme arthritis and 6 patients with other forms of chronic inflammatory arthritis, primarily rheumatoid arthritis. The tissue sections were subjected to chemical and immunostaining, and IgG antibody responses to ECGF were determined by enzyme‐linked immunosorbent assay (ELISA). Each finding was ranked for statistical analysis. Results In each disease, synovial tissue showed synovial hypertrophy, vascular proliferation, immune cell infiltrates, and fibrosis. However, among the 14 patients with antibiotic‐refractory arthritis, 8 (57%) had obliterative microvascular lesions in the tissue, compared with none of the 6 patients with other forms of chronic inflammatory arthritis (P = 0.04). Among the patients with Lyme arthritis, 5 (36%) had autoantibody responses to ECGF, and all 5 had obliterative lesions, as compared with only 3 of 9 patients who lacked ECGF antibody responses (P = 0.009). Moreover, the magnitude of ECGF antibody responses correlated directly with the extent of obliterative lesions (P = 0.02) and with greater vascularity in the tissue (P = 0.05). Conclusion The correlations of ECGF autoantibody reactivity with obliterative microvascular lesions imply that these autoantibodies may be involved in the obliterative process, suggesting that anti‐ECGF antibodies have specific pathologic consequences in the synovial tissue of patients with antibiotic‐refractory Lyme arthritis.